Endocytosis inhibitors block SARS-CoV-2 pseudoparticle infection of mink lung epithelium - Song, Ann; Phandthong, Rattapol; Talbot, Prue (Frontiers in Microbiology, 2023)
Both spill over and spill back of SARS-CoV-2 virus have been reported on mink farms in Europe and the United States. Zoonosis is a public health concern as dangerous mutated forms of the virus could be introduced into the human population through spillback. The purpose of our study was to determine the SARS-CoV-2 entry mechanism using the mink lung epithelial cell line (Mv1Lu) and to block entry with drug inhibitors. Mv1Lu cells were susceptible to SARS-CoV-2 viral pseudoparticle infection, validating them as a suitable disease model for COVID-19. Inhibitors of TMPRSS2 and of endocytosis, two pathways of viral entry, were tested to identify those that blocked infection. TMPRSS2 inhibitors had minimal impact, which can be explained by the apparent lack of activity of this enzyme in the mink and its localization within the cell, not on the cell surface. Dyngo4a, a small molecule endocytosis inhibitor, significantly reduced infection, supporting the conclusion that the entry of the SARS-CoV-2 virus into Mv1Lu cells occurs primarily through endocytosis. The small molecule inhibitors that were effective in this study could potentially be used therapeutically to prevent SARS-CoV-2 infection in mink populations. This study will facilitate the development of therapeutics to prevent zoonotic transmission of SARS-CoV-2 variants to other animals, including humans.